2022
DOI: 10.1172/jci140508
|View full text |Cite
|
Sign up to set email alerts
|

Wnt activation promotes memory T cell polyfunctionality via epigenetic regulator PRMT1

Abstract: T cell polyfunctionality is a hallmark of protective immunity against pathogens and cancer, yet the molecular mechanism governing it remains mostly elusive. We found that canonical Wnt agonists inhibited human memory CD8 + T cell differentiation while simultaneously promoting the generation of highly polyfunctional cells. Downstream effects of Wnt activation persisted after removal of the drug, and T cells remained polyfunctional following subsequent cell division, indicating the effect … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
10
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 16 publications
(12 citation statements)
references
References 52 publications
0
10
0
Order By: Relevance
“…Canonical WNT signaling affecting the β-catenin-TCF7 (Tcf-1) complex in CD8+ T and Treg cells enhances inflammation in part through up-regulation of proinflammatory cytokines, such as IFNγ and TNF [ 71 , 72 ]. In addition, WNT ligands, such as WNT3A, WNT5A, WNT10A and WNT10B, are up-regulated in inflamed tissues through proinflammatory signaling affecting the NF-κB (nuclear factor enhancer of immunoglobulin κ light chain of activated B cells) and STAT3 (signal transducer and activator of transcription 3) transcription factors [ 73–75 ].…”
Section: Immune-landscape Plasticitymentioning
confidence: 99%
See 1 more Smart Citation
“…Canonical WNT signaling affecting the β-catenin-TCF7 (Tcf-1) complex in CD8+ T and Treg cells enhances inflammation in part through up-regulation of proinflammatory cytokines, such as IFNγ and TNF [ 71 , 72 ]. In addition, WNT ligands, such as WNT3A, WNT5A, WNT10A and WNT10B, are up-regulated in inflamed tissues through proinflammatory signaling affecting the NF-κB (nuclear factor enhancer of immunoglobulin κ light chain of activated B cells) and STAT3 (signal transducer and activator of transcription 3) transcription factors [ 73–75 ].…”
Section: Immune-landscape Plasticitymentioning
confidence: 99%
“…It is not appropriate to predict ICI response based on WNT-related genetic alterations because such alterations are present in cases with the T-cell inflamed signature and stroma/EMT/TGFβ signature. Although the context-dependent immune regulation by WNT signaling cascades [ 71–81 ] and the unknown risk–benefit ratio of WNT signaling inhibitors [ 39 ] are limiting factors, phase I or II clinical trials of combination ICI therapy with WNT signaling inhibitors or WNT-related biologics ( Table 1 ) are ongoing and aim to reveal new avenues for immunotherapy in cancer.…”
Section: Immune-landscape Plasticitymentioning
confidence: 99%
“…As discussed above, modification of vital epigenetic enzymes can reprogram the T cell differentiation status and effector functions, which can be used to potentiate antitumor T cell functions (Tables 1 and 2 ). 65 , 66 , 67 , 68 Although epigenetic profiles affect the activity of transcription factors, accumulating evidence suggests that several transcriptional regulators can also modulate epigenetic profiles. For instance, the transcription factor TOX orchestrates the epigenetic landscape of exhausted T cells.…”
Section: Discussionmentioning
confidence: 99%
“…In the analysis of TME, low expression of DLX2 was associated with various tumor-infiltrating immune-positive cells like activated CD4/CD8 T cells, memory CD4/CD8 T cells, M1, etc. Research has found activation of Wnt signaling pathway suppressed the proliferation of CD8 + memory T cells and differentiation of effector T cell, generated CD8 + memory stem cells and enhanced the polyfunctionality of memory CD8 + T cell [ 52 54 ]. DLX2 functions as a transcription factor of Wnt signaling pathway, which can partly explain the more abundant infiltration of immune-enhancing cells in DLX2 low expression group.…”
Section: Discussionmentioning
confidence: 99%